Development of a thermally conductive and antimicrobial nanofibrous mat for the cold chain packaging of fruits and vegetables. (September 2022) - Shen, Chaoyi; Yang, Zhichao; Rao, Jingshan; Li, Jiangkuo; Wu, Di; He, Yong; Chen, Kunsong
Graphical abstract: Highlights: Boron nitride nanosheets/polycaprolactone/chitosan nanofibrous mats were rapidly developed by solution blow spinning. The boron nitride nanosheets/polycaprolactone/chitosan mats showed prominent thermal conductivity and a rapid response to heat. The boron nitride nanosheets/polycaprolactone/chitosan mats exhibited a hydrophobic surface and good antimicrobial activity. The incorporation of boron nitride nanosheets improved the thermal stability and water vapor barrier property of the polycaprolactone/chitosan mats. Abstract: Improving the thermal conductivity of antimicrobial packaging materials is important for transferring the respiratory heat produced by fruits and vegetables during the cold chain process, leading to enhanced cooling efficiency and reduction of postharvest losses. In this work, solution blow spinning (SBS) was used to rapidly develop boron nitride/polycaprolactone (PCL)/chitosan (CS) nanofibrous mats. The results show that the in-plane and cross-plane thermal conductivities of the boron nitride nanosheet (BNNS)/PCL/CS mats were 1.403 and 0.826 W m −1 K −1, respectively, which were 2.4 and 1.4 times those of the control group, showing the rapid response of the developed mats to heat during a 40 s heating process. Morphology results show that BNNSs were evenly stacked on the PCL/CS nanofibers in physics mode. With the incorporation of BNNSs, the thermal stability and water vapor barrier property of the developed mats were improved, and the average diameter of the nanofibers decreased from 385.6 nm to 221.0 nm. Moreover, the developed mats exhibited good antimicrobial activity in vitro and possessed hydrophobic surfaces. This work shows that the BNNS/PCL/CS nanofibrous mats developed by SBS are a promising packaging material for a green and sustainable cold chain of fruits and vegetables.